Endoscopia Y Endocirugia En Clínica Veterinaria (2024)
This internship was carried out at the company specialized in minimally invasive surgery (ECMV VETERINARIAS), from August 8, 2023 to June 7, 2024, with a total duration of 350 hours. The main objective was to strengthen the theoretical and practical knowledge acquired throughout the career. During the internships, the patients treated were mostly companion animals (97%), among them canines and felines, canines predominated (64%), while felines (34%).